2012
DOI: 10.1210/en.2012-1528
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Cyclin D3 Improves Decidualization Defects in Hoxa-10−/− Mice

Abstract: Uterine decidualization, a crucial process for implantation, is a tightly regulated process encompassing proliferation, differentiation, and polyploidization of uterine stromal cells. Hoxa (Homeobox A)-10, a homeobox transcription factor, is highly expressed in decidualizing stromal cells. Targeted gene deletion experiments have demonstrated marked infertility resulting from severely compromised decidualization in Hoxa-10(-/-) mice. However, the underlying mechanism by which Hoxa-10 regulates stromal cell diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…2,23 The present study showed that Hmgn1 could stimulate the expression of Prl8a2 and Prl3c1 which were 2 well-known markers for decidual cell differentiation. Taken together, these results revealed an important role of Hmgn1 in maintaining the proliferation and differentiation of uterine stromal cells during decidualization.…”
Section: Discussionmentioning
confidence: 54%
“…2,23 The present study showed that Hmgn1 could stimulate the expression of Prl8a2 and Prl3c1 which were 2 well-known markers for decidual cell differentiation. Taken together, these results revealed an important role of Hmgn1 in maintaining the proliferation and differentiation of uterine stromal cells during decidualization.…”
Section: Discussionmentioning
confidence: 54%
“…Further analysis demonstrated that Egr2 was required for the HB‐EGF function in stromal cell differentiation by this evidence that siRNA‐mediated knockdown of Egr2 impeded the stimulation of rHB‐EGF on the expression of Prl8a2 , Prl3c1 , and Pgr . Previous studies have found that HB‐EGF could facilitate uterine decidualization by upregulating Ccnd3 , which was a key cell cycle regulator in stromal cell proliferation and differentiation (Sroga, Gao, Ma, & Das, ; Tan et al., ). Attenuation of Egr2 expression in stromal cells abrogated the induction of Ccnd3 elicited by rHB‐EGF, suggesting that Egr2 may serve as an intermediate to mediate the regulation of HB‐EGF on Ccnd3 .…”
Section: Discussionmentioning
confidence: 98%
“…Among various cell cycle related molecules including various cyclins, CDKs and cell cycle inhibitors, cyclin D3, a well-known regulator of mammalian cell proliferation [46], has been shown to be highly expressed in the decidualizing stromal cells within implantation chambers and essential for normal postimplantation uterine decidualization [47,48]. Previous studies demonstrated that many key signaling and regulatory molecules such as heparin-binding EGF-like growth factor (HB-EGF) [49], interleukin 11-interleukin 11 receptor alpha (IL11-IL11Rα) [50,51], Hox family transcription factor HOXA10 [52], Kruppel-like factor 9 (KLF9, previously known as BTEB1) [53], death effector domain-containing protein (DEDD) [54] were considered to regulate decidualization at least partially through cyclin D3. In this respect, we added a new line of evidence showing that Rbbp7 is critical for normal cyclin D3 expression in mESCs during decidualization.…”
Section: Discussionmentioning
confidence: 99%